2007
DOI: 10.1126/science.1145950
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in the Structure of the ABC Transporter-Binding Protein Complex BtuCD-BtuF

Abstract: BtuCD is an adenosine triphosphate-binding cassette (ABC) transporter that translocates vitamin B12 from the periplasmic binding protein BtuF into the cytoplasm of Escherichia coli. The 2.6 angstrom crystal structure of a complex BtuCD-F reveals substantial conformational changes as compared with the previously reported structures of BtuCD and BtuF. The lobes of BtuF are spread apart, and B12 is displaced from the binding pocket. The transmembrane BtuC subunits reveal two distinct conformations, and the transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
290
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(313 citation statements)
references
References 25 publications
17
290
1
3
Order By: Relevance
“…In contrast to the ATPases, the structures of the integral membrane subunits are not universally conserved among ABC transporters. Four different structural classes have been discovered, which probably have different mechanisms of substrate translocation (see the figure): type I importers (which are exemplified by the maltose transporter MalEFGK 2 from Escherichia coli [57][58][59][60][61] ; Protein Data Bank (PDB) accession 2R6G); type II importers (exemplified by vitamin B 12 transporter BtuC 2 D 2 F from E. coli [62][63][64] ; PDB accession 4FI3); exporters (such as multidrug and peptide transporters [65][66][67] , exemplified by the drug exporter TM287/288) from Thermotoga maritima; PDB accession 3QF4); and ECF transporters (such as ECF-FolT from Lactobacillus brevis for folate transport 21 ; PDB accession 4HUQ). Type I and II importers and energy-coupling factor (ECF) transporters are only found in prokaryotes, whereas exporters are found in all kingdoms of life 28 .…”
Section: Box 1 | Diversity Of Abc Transportersmentioning
confidence: 99%
“…In contrast to the ATPases, the structures of the integral membrane subunits are not universally conserved among ABC transporters. Four different structural classes have been discovered, which probably have different mechanisms of substrate translocation (see the figure): type I importers (which are exemplified by the maltose transporter MalEFGK 2 from Escherichia coli [57][58][59][60][61] ; Protein Data Bank (PDB) accession 2R6G); type II importers (exemplified by vitamin B 12 transporter BtuC 2 D 2 F from E. coli [62][63][64] ; PDB accession 4FI3); exporters (such as multidrug and peptide transporters [65][66][67] , exemplified by the drug exporter TM287/288) from Thermotoga maritima; PDB accession 3QF4); and ECF transporters (such as ECF-FolT from Lactobacillus brevis for folate transport 21 ; PDB accession 4HUQ). Type I and II importers and energy-coupling factor (ECF) transporters are only found in prokaryotes, whereas exporters are found in all kingdoms of life 28 .…”
Section: Box 1 | Diversity Of Abc Transportersmentioning
confidence: 99%
“…All but one correspond to bacterial transporters. Five are ABC importers (BtuCD, ModBC-A, HI1470/1, MalFG/ K, MetNI), [9][10][11][12][13][14][15] and three are drug exporters (SAV1866, MsbA, and mouse P-glycoprotein). [16][17][18][19] High-resolution structures and NMR, EPR, and electron microscopy data strongly suggest that ABC exporters undergo large movements during substrate efflux, in particular upon ATP binding and/or hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, two more crystal structures have been determined, one of the homologous HIF protein (HI1470/71) from Haemophilus influenzae (Pinkett et al 2007), and that of the BtuCD protein in complex with the binding protein BtuF (Hvorup et al 2007; figure 5b). The structures of BtuCD, HIF and BtuCD-F demonstrated that a subset of TM helices (3-5a) can adopt one of two conformations (figure 5c).…”
Section: Type II Abc Importersmentioning
confidence: 99%